Asian Food Co. Ltd. / Wan Aisyah Amni Wan Mohd Saferdin ... [et al.] - Wan Mohd Saferdin, Wan Aisyah Amni; Syed Izaddin, Sharifah Nur Haslina; Mat Nor, Nor Saa'dah; Abdul Malik, Zainab (Faculty of Office Management & Technology, 2006)
Bangkok, Thailand has been chosen as our company destination to export our product. The company has selected Thailand to market our product not only Thailand is nearer to our country but it is because of a few factors such as demand factors, strategic factors, regulatory/economic factors, sociopolitical factors and also some other factors. With a variety of over 100 products, our exquisite Asian Ethnic Sauces are blended form an almost endless list of selected quality natural spices, herbs and vegetables to provide the original Asian flavors. Originating form Malay, Indian, Chinese, Thai and Vietnamese heritage among other, our products are convenient to use. Our products are available with two different flavors which are Asian Meal Curry Sauce and Asian Meals Oriental Sauces. Each of these flavors available with different types of sauces where it can be used for different types of meal. For example, Asian Meals Curry Sauce available with Asian Meals Duyung Curry Sauce, Asian Meals Malay Red Curry Paste, Asian Meals Laksa Curry Paste, Asian Meals Meat Curry Paste, Asian Meals Rendang Curry Paste and so on. While for the Asian Meals Oriental Sauces, it available with Asian Meals Black Pepper Sauces, Asian Meals Oriental BBQ Sauces, Asian Meals Oriental Hoi Sin Sauce, Asian Meals Sambal Tumis, Asian Meals Sweet & Sour and other more.